SELF-FORGIVENESS DAN KESEJAHTERAAN PSIKOLOGIS PADA NARAPIDANA LEMBAGA PEMASYARAKATAN KELAS 2A AMBARAWA - Daniel Panggabean; Arthur Huwae (Journal of Psychology and Instruction, 2023)
While serving his sentence, the convict will be placed in a Correctional Institution (LP). In Indonesia, these places experience overcapacity which can result in overcrowding of prisoners. These limitations on space and movement are also experienced by inmates at class 2A Ambarawa prison which results in inmates experiencing psychological problems such as low self-acceptance, feelings of guilt, and difficulty forgiving themselves. This can prevent the achievement of psychological well-being in prisoners while serving their sentence in Class 2A Ambarawa Penitentiary. Therefore, this study aims to examine the relationship between self-forgiveness and the psychological well-being of class 2A Ambarawa prison inmates. This study uses a quantitative method with a correlational design. A total of 178 participants were involved using the sample random sampling technique. The research measurement used the self-forgiveness scale (a=0.894) and psychological well-being, it was measured using the Ryff Psychological Well-Being Scale (a=0.843). The results of the study proved that there was a significant positive relationship between self-forgiveness and psychological well-being in Class 2A Ambarawa Penitentiary inmates (r = 0.618 and a significant 0.000). This indicates that self-forgiveness is one of the factors related to the psychological well-being of class 2A Ambarawa Penitentiary inmates. This indicates that self-forgiveness is one of the factors related to improving the psychological well-being of inmates at Class 2A Penitentiary in Ambarawa. This research implies that it is hoped that convicts who are serving a period of detention will be able to increase their self-forgiveness so that they can overcome and survive feelings of guilt, and anxiety while still being able to achieve psychological well-being in their lives.